2005
DOI: 10.1097/01.ju.0000158072.31086.af
|View full text |Cite
|
Sign up to set email alerts
|

An Artificial Somatic-Autonomic Reflex Pathway Procedure for Bladder Control in Children With Spina Bifida

Abstract: The artificial somatic-autonomic reflex arc procedure is an effective and safe treatment to restore bladder continence and reverse bladder dysfunction for patients with spina bifida.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
56
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(63 citation statements)
references
References 8 publications
5
56
0
2
Order By: Relevance
“…Of course, we are deeply disappointed that none of our patients were able to achieve the dramatic voluntary bladder control that has been described by Xiao and colleagues. 6,7 Our study certainly has limitations, but our results are in agreement with 2 recently published studies of the Xiao procedure in adults with neurogenic bladder dysfunction related to spinal cord injury. Rasmussen et al 4 in Denmark and Sievert et al 5 in Austria both reported a similar lack of effectiveness of the Xiao procedure in their patients with spinal cord injury in very well-designed studies.…”
supporting
confidence: 82%
“…Of course, we are deeply disappointed that none of our patients were able to achieve the dramatic voluntary bladder control that has been described by Xiao and colleagues. 6,7 Our study certainly has limitations, but our results are in agreement with 2 recently published studies of the Xiao procedure in adults with neurogenic bladder dysfunction related to spinal cord injury. Rasmussen et al 4 in Denmark and Sievert et al 5 in Austria both reported a similar lack of effectiveness of the Xiao procedure in their patients with spinal cord injury in very well-designed studies.…”
supporting
confidence: 82%
“…[16][17][18] Buoyed by the success of the Xiao procedure in patients with spinal cord injury, Xiao et al also applied the technique to children with neurogenic bladder dysfunction related to spina bifida. 36 In 2005, Xiao et al reported that 17 (85%) of 20 children with spina bifida who underwent the procedure had "satisfactory bladder control and continence within 8 to 12 months." 36 Xiao et al described these improvements in bladder function as "remarkable," noting that all but 1 of the patients who voided voluntarily did not even need to initiate the reflex by scratching themselves in the dermatomal distribution of the donor nerve root to empty their bladders.…”
mentioning
confidence: 99%
“…36 In 2005, Xiao et al reported that 17 (85%) of 20 children with spina bifida who underwent the procedure had "satisfactory bladder control and continence within 8 to 12 months." 36 Xiao et al described these improvements in bladder function as "remarkable," noting that all but 1 of the patients who voided voluntarily did not even need to initiate the reflex by scratching themselves in the dermatomal distribution of the donor nerve root to empty their bladders. 36 As of 2012, Xiao reported that he and his group had performed the Xiao procedure on 1890 patients with spina bifida in China.…”
mentioning
confidence: 99%
“…Peters [48] and Xiao [49,50] demonstrated that the skin-central nervous reflex pathway system following endto-end anastomosis of L5 VR (somatic nerves) to S2/S3 VR (autonomic nerve) could recover controllable voiding function in the clinical trial. However, this method of nerve anastomosis had obvious injury to the donor nerve and affects the donor nerve of somatic motor function.…”
Section: The Advantages Of Terminolateral Neurorrhaphy Of Autonomic-smentioning
confidence: 99%